Sex matters: how stress at different life stages affects males and females differently - Martín-Aguiar, Víctor; Muñoz-Martín, José; Ramírez-Pérez, Cristina; Chaves-Peña, Patricia; Zea-Doña, Alejandro; Infantes-López, M. Inmaculada; Pérez-Martín, Margarita; Pedraza-Benítez, María del Carmen (My University, 2025)
Early stress episodes are known to affect brain development and are related to increased risk of developing stress-induced depression later in life through inflammation processes. There is an important gender factor in the vulnerability to stress-induced depression after exposure to stress in critical developmental windows, with the juvenile period being one of them. Plus, the prevalence of depression is higher in females. However, despite its relevance, investigations about the sexual differences in this process are scarce. Our goal is to study how juvenile and/or adult stress could affect depression-like behaviors in male and female mice. For this purpose, four experimental groups of both male and female mice of strain C57BL/6J (N=71, 32 male, 39 female) were used: control (C), juvenile (JE), adult (AE), and double stress with a combination of juvenile and adult stress (DE). Depression-like behaviors were evaluated in the adult period together with physiological measurements. Open field test was used to study exploratory behaviors and patterns, an object-based attention test (OBAT) was used to study short and long-term memory, and a nest-building test to assess motivation and fatigue. Plus, a corticosterone ELISA was performed to study the HPA axis response (basal, 10 and 60 minutes after a physical stressor and terminal moment). Finally, a PCA was performed to integrate the results. Taken together, our results suggest that juvenile and/or adult stress affects mice differently, as males seem more affected by adult stress and females are more affected by juvenile stress.
Keywords: Estrés (Fisiología) - Diferencias sexuales; Stress; Sexual differences; Behaviors